A Relapsing Immune Thrombocytopenia Case in a Patient Following COVID-19 Vaccination - Tel, Burcin Meryem Atak; Kahveci, Gizem; Duman, Tuba Taslamacioglu; Kurtkulagi, Özge; Bilgin, Satilmis; Senturk, Hilal; Akin, Havva; Aktas, Gulali (Journal of Health and Allied Sciences NU, 2021)
There are several vaccines developed against COVID-19 infection. Inactivated viral vaccines are usually well tolerated. We aimed to present a relapsing immune thrombocytopenia case following inactive COVID-19 vaccine. Here we report a case of relapsing immune thrombocytopenia following inactivated viral vaccine against COVID-19 in a 60-year-old woman with a history of immune thrombocytopenia. The patient responded well to dexamethasone treatment and was discharged from the hospital with full recovery. We suggest that physicians seek the history of a recent inactivate COVID-19 vaccine shot in patients with immune thrombocytopenia.
Keywords: COVID-19; immune thrombocytopenia; inactivated viral vaccine